2021
DOI: 10.21608/puj.2021.75319.1120
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and neuropsychiatric changes in experimental chronic toxoplasmosis: Histopathological and immunohistochemical studies

Abstract: Background: T. gondii is an intracellular protozoan parasite that can establish a latent infection in the central nervous system that may develop into chronic inflammation resulting in neurobehavioral problems in the host. The processes behind these alterations are still largely mysterious. Objective: Detection of behavioral, histopathological and immunohistochemical changes in mice infected by T. gondii Me49 strain. Material and Methods: A total of 105 adult male Swiss albino mice were divided into 60 used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…Previous study found varying degrees of perivascular and interstitial inflammatory infiltrates, astrocytosis, degenerating neurons, and meningitis. 56 Microglia and occasional encysted bradyzoites were observed pathologically. Parenchymal infiltrates of inflammatory cells, primarily lymphocytes, were found to be mild, moderate, and intense and to progress with time.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study found varying degrees of perivascular and interstitial inflammatory infiltrates, astrocytosis, degenerating neurons, and meningitis. 56 Microglia and occasional encysted bradyzoites were observed pathologically. Parenchymal infiltrates of inflammatory cells, primarily lymphocytes, were found to be mild, moderate, and intense and to progress with time.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the level of expression of this molecule was increasingly reduced in the chronic phase of infection from the 7th to 12th weeks in brain tissue of mice infected with toxoplasmosis compared to non-infected control [ 98 ]. CD138 (syndecan-1), which is increased during antibody-secreting cells (ASCs) maturation, is needed for mounting an efficient long-term humoral immune response by promoting survival of ASCs in a cell-intrinsic manner [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…El-team Temsahy's team [95] also made similar observations. Etewa's group [96] showed that Infected mice had neurobehavioral problems.…”
Section: Discussionmentioning
confidence: 99%